(untitled) (American Journal of Pedagogical and Educational Research, 2022)
In the article, methodological-didactic bases, principles, laws, psychological-pedagogical possibilities of forming the first invariant and variable concepts of nature in elementary school students, previous ideas on the formation of the first invariant and variable concepts of nature in elementary school students, formation of the first invariant and variable concepts of nature in students information about the different levels is given.